2014
DOI: 10.5194/sed-6-1723-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upper mantle structure around the Trans-European Suture Zone obtained by teleseismic tomography

Abstract: Abstract. The presented study aims to resolve the upper mantle structure around the Trans-European Suture Zone (TESZ) which is the major tectonic boundary in Europe. The data of 183 temporary and permanent seismic stations operated during the period of the PASsive Seismic Experiment PASSEQ 2006–2008 within the study area from Germany to Lithuania was used to compile the dataset of manually picked 6008 top quality arrivals of P waves from teleseismic earthquakes. We used the non-linear teleseismic tomography al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 68 publications
(72 reference statements)
4
5
0
Order By: Relevance
“…9c). This general finding coincides with the results by Koulakov et al (2009) who reported the sharp transition along the TESZ from the negative amplitudes, characterizing the young tectonic features of central-western Europe, to positive ones beneath the old EEC. Moreover, a sharp transition from low to high shear-wave velocities between the Phanerozoic Europe and EEC, respectively, was observed from waveform inversion of both body and surface waves by Zielhuis and Nolet (1994).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…9c). This general finding coincides with the results by Koulakov et al (2009) who reported the sharp transition along the TESZ from the negative amplitudes, characterizing the young tectonic features of central-western Europe, to positive ones beneath the old EEC. Moreover, a sharp transition from low to high shear-wave velocities between the Phanerozoic Europe and EEC, respectively, was observed from waveform inversion of both body and surface waves by Zielhuis and Nolet (1994).…”
Section: Resultssupporting
confidence: 81%
“…The observed velocity perturbations down to about 120 km beneath Poland are about 2 to 3 % higher with respect to the IASP91 velocity model, while going deeper the variations are slightly smaller, which most likely indicates some effects due to the applied crustal TT corrections. The higher velocity values in this area are observed down to about 200 km, which coincides well with the studies by WildePiórko et al (2010), Majorowicz et al (2003) and Koulakov et al (2009). Legendre et al (2012) found the highest velocity values in the mantle of the EEC at about 150 km depth.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations